2011
DOI: 10.1002/j.2050-0416.2011.tb00446.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Ethanol, Carbonation and Hop Acids on Volatile Delivery in a Model Beer System

Abstract: A model beer was created to investigate the effects of ethanol, carbonation and hop acids on volatile release (ethyl acetate, isoamyl alcohol and phenethyl alcohol) using both headspace analysis and in-nose measurement during consumption. None of the factors were found to impact on equilibrium headspace partitioning, however headspace sampling after short term decanting revealed minor and compound specific effects of each of the components. When measured in-vivo, hop acids had no significant effect on volatile… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
19
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 40 publications
(27 citation statements)
references
References 21 publications
(37 reference statements)
3
19
1
Order By: Relevance
“…The nondiscriminating attributes will not be discussed further. Consequently, the increases in volatile release caused by ethanol and carbonation as previously found in our laboratory (Clark et al 2011) do not appear to result in perceivable differences in these samples. Viscosity was also a non-discriminating attribute, which is not surprising as it is very difficult for the human palate to significantly discriminate between Newtonian fluids (i.e.…”
Section: Resultsmentioning
confidence: 64%
See 1 more Smart Citation
“…The nondiscriminating attributes will not be discussed further. Consequently, the increases in volatile release caused by ethanol and carbonation as previously found in our laboratory (Clark et al 2011) do not appear to result in perceivable differences in these samples. Viscosity was also a non-discriminating attribute, which is not surprising as it is very difficult for the human palate to significantly discriminate between Newtonian fluids (i.e.…”
Section: Resultsmentioning
confidence: 64%
“…Results from experiments investigating volatile release from the matrix into the headspace at static equilibrium (Aznar et al 2004;Hewson 2007) differ considerably from those under dynamic conditions (where the headspace is diluted by air at a constant rate) (Pozo-Bayon et al 2009;Saint-Eve et al 2009) and from the breath during consumption (Clark et al 2011). Sugars (Friel et al 2000;Hewson et al 2008;SaintEve et al 2009) and isomerised hop acid products (Clark et al 2011) have not been shown to have an effect on volatile partitioning at the concentrations commonly found in beer and other beverages.…”
Section: Introductionmentioning
confidence: 91%
“…However, these results showed the same trend; an enhancement of aroma release in presence of ethanol. Recently, Clark et al (2011) also showed by using in vivo-API-MS a similar rise in the release of three targeted aroma compounds during the in vivo consumption of flavored model beers with an increase in the ethanol content from 0 to 4.5 mL L À1 . Contrarily, most of the studies dealing with the effect of ethanol on aroma release performed in static conditions have shown a reduction in the aroma released into the headspace.…”
Section: Impact Of Ethanol and Sugar On In Vivo Aroma Release During mentioning
confidence: 80%
“…These iso‐ α ‐acids and their chemically modified variants play a disproportionately large role in the final quality of beer . Ageing also has a significant influence on the consistency of beer bitterness and can be attributed to the decomposition of its components . The iso‐ α ‐acids, derived from the flowers of the hop plant ( Humulus lupulus ), give beer its bitter taste and exert bacteriostatic effects on most Gram‐positive bacteria due to their ability to dissipate the proton motive force …”
Section: Introductionmentioning
confidence: 99%
“…5 Ageing also has a significant influence on the consistency of beer bitterness 2 and can be attributed to the decomposition of its components. 6 The iso-α-acids, derived from the flowers of the hop plant (Humulus lupulus), give beer its bitter taste and exert bacteriostatic effects on most Gram-positive bacteria due to their ability to dissipate the proton motive force. 4,7 -9 The chemistry behind the ageing process is extremely complex, as many constituents are derived from the raw materials or formed during the production process.…”
Section: Introductionmentioning
confidence: 99%